Kamusi ya methali : maana na matumizi - Mkota, Abel. (Nairobi : Vide-Muwa Publishers, 2009)
A dictionary of Swahili proverbs and their usage.
Includes bibliographical references (p. ix).
In Swahili.
Keywords: Proverbs, Swahili